Analysis of Macroeconomic Variables on the Existence of Inflation in Indonesia Using the Vector Error Correction Model Approach - Afrizal (Jurnal Ekonomi Kuantitatif Terapan, 2024)
This research investigates the impact of macroeconomic variables, namely money supply,exchange rate, interest rate, and the joint stock index, on inflation in Indonesia. Employing theVector Error Correction Model (VECM) dynamic model approach, the study reveals a long-termrelationship among each variable (Inflation Rate, Jakarta Composite Index, Interest Rate,Exchange Rate, and Money Supply). Granger Causality Test results indicate a unidirectionalrelationship of interest rate and money supply variables to inflation, interest rate to JakartaComposite Index, and money supply to the exchange rate. Conversely, there is a bidirectionalrelationship between exchange rate and inflation variables. In the short term, Interest Ratesignificantly and positively influences inflation, whereas, in the long term, it exhibits a negativeand insignificant effect. Money supply, in the long run, significantly and positively affects theinflation rate. This study stands out in the macroeconomic literature due to its distinctive choiceof variables and the dynamic model employed.